A General Configuration Antenna Array for Multi-User Systems with Genetic and Ant Colony Optimization - Rahhal, Jamal S.; Abu-Al-Nadi, Dia I. (Electromagnetics, 2007)
Antenna arrays are used in the CDMA-based cellular systems in order to increase the systems capacity. Different approaches benefit from the spatial separation between users. Smart and adaptive beam antennas are the best proposed solution for these systems. Several methods are used to provide the system with a radiation pattern that increases the signal-to-interference ratio (C/I). Antenna configuration is the way the array elements are distributed in space. This distribution can influence the design of the beam formation or the adaptation method, such that, the calculation of the different parameters requires a known array configuration. Antenna configuration is discussed in several research papers including planar arrays and circular arrays. Here, we introduce a general antenna array structure and derived its optimal parameters, and then we optimize the solution under different quantization errors using a genetic algorithm (GA) and an ant colony optimization (ACO). Results showed that we can configure the antenna array to provide an acceptable C/I. Also, results showed that we can obtain a good solution that is less sensitive to quantization errors using the ACO.